Chapter Stand structure and natural regeneration in a coastal Stone pine (Pinus pinea L.) forest in Central Italy - Travaglini, Davide (Monitoring of Mediterranean Coastal Areas: Problems and Measurement Techniques, 2022)
This study was carried out in the Regional Park of San Rossore (Italy) where we found natural regeneration of Stone pine (Pinus piena L.) in an even-aged stand of pine. The objectives of our study were to characterize the forest structure of the Stone pine stand and to quantify the natural regeneration of pine. Our results show that natural regeneration of P. pinea in the Park of San Rossore is a reachable target, however an adequate management is needed. The results are discussed with the intention of providing knowledge to support management of Stone pine forests along the Tyrrhenian coast.